(untitled) (ARSY : Jurnal Aplikasi Riset kepada Masyarakat, 2025)
The Student Work Lecture (KKM) Group 62 of Bina Bangsa University (UNIBA) held a socialization program on the implementation of anti-bullying values in commemoration of National Children’s Day at SDN 2 Sukamarga. This program aims to increase students’ awareness and understanding of the importance of mutual respect, prevent bullying behavior, and create a safe and comfortable school environment. Implementation methods included interactive counseling, educational games, and group discussions involving students, teachers, and parents. The results of the activity showed an increase in students’ understanding of the negative impacts of bullying and a growing shared commitment to creating an anti-bullying culture in schools. This activity is expected to be a sustainable step in building children’s character with empathy and high integrity.